2009
DOI: 10.1016/j.molmed.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases in male reproductive function

Abstract: Recent studies have shown that male reproductive function is modulated via the mitogen-activated protein kinase (MAPK) cascade. The MAPK cascade is involved in numerous male reproductive processes, including spermatogenesis, sperm maturation and activation, capacitation and acrosome reaction, before fertilization of the oocyte. In this review, we discuss the latest findings in this rapidly developing field regarding the role of MAPK in male reproduction in animal models and in human spermatozoa in vitro. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 78 publications
3
120
0
Order By: Relevance
“…Previously, it was reported that the MPAKs play an important role in spermatogenesis (6), with MAPK1 predicted to phosphorylate 47 (ϳ44%) proteins in the sub-KSPN (supplemental Fig. S4).…”
Section: Reconstruction Of the Testicular Kspn And Analysis Of The Spmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, it was reported that the MPAKs play an important role in spermatogenesis (6), with MAPK1 predicted to phosphorylate 47 (ϳ44%) proteins in the sub-KSPN (supplemental Fig. S4).…”
Section: Reconstruction Of the Testicular Kspn And Analysis Of The Spmentioning
confidence: 94%
“…Because phosphorylation, an important and ubiquitous post-translational modification (PTM) 1 , is one of the most critical regulatory mechanisms of the cell cycle (5), which is particularly active during spermatogenesis, a number of pioneering studies have contributed to our understanding of phosphoregulation in spermatogenesis. For example, mitogen-activated protein kinases (MAPKs) such as ERK1/2, were found to play an important role in ectoplasmic specialization dynamics during spermatogenesis (6). As important regulators of the cell cycle (7,8), the POLOlike kinases (PLKs) especially PLK1, were found to be required at multiple stages of spermatogenesis (9 -12).…”
mentioning
confidence: 99%
“…Introduction. Studies in multiple epithelia and/or blood-tissue barriers in various organs (e.g., kidney, small intestine, brain, eyes), including the BTB in adult mammalian testes, have demonstrated the role of cytokines, such as TNF␣, interferon-␥, TGF-␤2/-␤3, IL-1␣, and IL-12, in regulating TJ permeability barrier function under normal and pathological conditions (e.g., inflammation, tumorigenesis) (Walsh et al, 2000;Xia et al, 2005a;Lui and Cheng, 2007;Li et al, 2008Li et al, , 2009aCapaldo and Nusrat, 2009;Turner, 2009;Marchiando et al, 2010a;Roberson and Bowcock, 2010;John et al, 2011). It is noted that endocytic vesicle-mediated protein trafficking events (e.g., endocytosis, transcytosis, recycling, or intracellular protein degradation mediated by endosome-and/or ubiquitin-dependent pathways) that determine the levels of integral membrane proteins at the TJ barrier play a critical role in modulating the adhesive status of cell adhesion protein complexes (e.g., cadherins, occludins, JAMs, claudins) at the barrier, and protein endocytosis can be mediated by either clathrinor caveolae-dependent pathways or macropinocytosis (Tuma and Hubbard, 2003;Maxfield and McGraw, 2004;Mehta and Malik, 2006;Clague and Urbé, 2010;Golachowska et al, 2010;Hsu and Prekeris, 2010).…”
Section: Cytokinesmentioning
confidence: 99%
“…The MAPK (Mitogen-activated protein kinase) pathway is involved in many male reproductive processes, including spermatogenesis, sperm maturation and activation, adhesion of Sertoli cells and spermatogenic cells, and dynamics of the blood-testis barrier [71]. Transcripts of rat Pdgfrb are detected at embryonic day 18 (E18), reach high levels on 5 dpn, and then decline to lower levels [72].…”
Section: Differential Expression Of Genes In Cellular Signaling Pathwaysmentioning
confidence: 99%